Safety Equipment Technology and Planned Maintenance Systems on the Performance of International Shipping Ship Crews - Belo, Gusty Tandy; Maemunah , Siti; Yuliantini, Yuliantini; Ricardianto, Prasadja; Thamrin, Muhammad (Dinasti Publisher, 2026)
Research related to safety training, planned maintenance systems, and safety equipment technology in influencing ship crew performance by mediating work competency. The research method is quantitative, the data analysis method used is SEM – PLS. Correspondence of 90 crew members from PT. Pertamina International Shipping. The research results show that safety training influences competence, namely increasing life safety at sea and reporting the position of the ship when sailing via radio and GPS. The maintenance system influences work competency, the findings show that the ship maintenance planning procedures are running well. Safety equipment technology significantly positively influences work competency. Planned safety training can improve the quality of ship operational performance. The arranged upkeep framework appears great transport support administration that underpins the smooth operation of the transport to progress the execution of the ship's team. Security gear innovation impacts the execution of dispatch group, finding ideal security gear contributes to moving forward security and team execution. Work competency intercedes the positive and critical impact of security preparing, arranged support frameworks and security gear innovation on transport group execution. Work competency plays an important role as a mediator in the relationship between safety training, planned maintenance systems, and safety equipment technology and the performance of ship crew at PT. Pertamina International Shipping.